2005
DOI: 10.1158/0008-5472.can-05-2138
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration and Breast Cancer: A Prospective Cohort Study

Abstract: Breast cancer incidence has increased during recent decades for reasons that are only partly understood. Prevalence of sleeping difficulties and sleepiness has increased, whereas sleeping duration per night has decreased. We hypothesized that there is an inverse association between sleep duration and breast cancer risk, possibly due to greater overall melatonin production in longer sleepers. This populationbased study includes information from women born in Finland before 1958. Sleep duration, other sleep vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(115 citation statements)
references
References 46 publications
6
106
3
Order By: Relevance
“…Finally, 12 articles fulfilling the inclusion criteria were included in the meta-analysis. Among these 12 articles, five studies reported breast cancer (Verkasalo et al, 2005;Pinheiro et al, 2006;Kakizaki et al, 2008b;Vogtmann et al, 2013;Wu et al, 2013), two studies on colorectal cancer (Jiao et al, 2013;Zhang et al, 2013), one each study on prostate cancer (Kakizaki et al, 2008a), endometrial cancer (Sturgeon et al, 2012), epithelial ovarian cancer (Weiderpass et al, 2012), thyroid cancer (Luo et al, 2013), and all type cancers (von Ruesten et al, 2012).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 12 articles fulfilling the inclusion criteria were included in the meta-analysis. Among these 12 articles, five studies reported breast cancer (Verkasalo et al, 2005;Pinheiro et al, 2006;Kakizaki et al, 2008b;Vogtmann et al, 2013;Wu et al, 2013), two studies on colorectal cancer (Jiao et al, 2013;Zhang et al, 2013), one each study on prostate cancer (Kakizaki et al, 2008a), endometrial cancer (Sturgeon et al, 2012), epithelial ovarian cancer (Weiderpass et al, 2012), thyroid cancer (Luo et al, 2013), and all type cancers (von Ruesten et al, 2012).…”
Section: Search Resultsmentioning
confidence: 99%
“…Two studies reported a U-shaped association between sleep duration and cancer risk (Jiao et al, 2013;Zhang et al, 2013); whereas other studies did not reveal such an association (Kakizaki et Hao Zhao 1,2,3& , Jie-Yun Yin 2& , Wan-Shui Yang 1 , Qin Qin 2 , Ting-Ting Li 2 , Yun Shi 2 , Qin Deng 1 , Sheng Wei 2 , Li Liu 2 *, Xin Wang 1 *, Shao-Fa Nie 2 * von Ruesten et al, 2012), or only found a null association (Verkasalo et al, 2005;McElroy et al, 2006;Pinheiro et al, 2006;Sturgeon et al, 2012;Luo et al, 2013). The mechanisms underlying the association between short or long sleep duration and cancer risk are not fully understood.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Based on this information, one can infer the great importance of having a bedroom that is very dark at night for proper circadian rhythm and sleep maintenance [62][63]. This task, given streetlights, car headlights, light from other buildings, and other sources of light pollution during the night, is perhaps even more difficult to achieve architecturally than delivering the correct amounts of light during the day, especially when one adds the caveat that morning light penetration into the bedroom is desirable.…”
Section: Discussion On the Limitations Of This Researchmentioning
confidence: 99%
“…Dr. Sturgeon et al [4] now provide the sixth study on the issues concerned and report mixed results. Overall, with regard to how long one sleeps, first [4][5][6][7][8]-but not all [9]-epidemiological evidence could be viewed in line with increased cancer risks in those who sleep less than others [2].…”
Section: Introductionmentioning
confidence: 99%